The effectiveness of the marketing communication in Telekom Training College (TTC), Jalan Gurney Kiri, Kuala Lumpur / Norhalilah Abdul Jalil - Abdul Jalil, Norhalilah (Faculty of Business and Management, 2005)
Nowadays, education institutions are continuously seeking better ways to communicate effectively and efficiently with their targeted audiences. The competition is more intense than ever, and the marketplace is filled with communications clutter. Marketing communicators are challenged to use communication methods that will break through this clutter to reach audiences with interesting and persuasive messages. In meeting these challenges, companies are embracing a strategy of Integrated Marketing Communication (IMC). Marketing communication activities is more effective when their strategies are base on knowledge of consumer behavior. The combination of appropriate IMC and consumer behavior will activates the consumer's decision process.